2023
DOI: 10.1088/1361-6463/acdd0c
|View full text |Cite
|
Sign up to set email alerts
|

Advanced materials for triboelectric nanogenerator

Abstract: Due to the advantages of excellent output power, low cost and easily preparation, triboelectric nanogenerator is developing rapidly in the field of renewable energy. The output performance of triboelectric nanogenerator is largely dependent on the surface charge density, which is closely related to the ability of the tribo-material to gain or lose electrons. To obtain higher output power, numerous efforts have been done on material modifications of the friction layer and electrodes of triboelectric nanogenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 135 publications
0
3
0
Order By: Relevance
“…Among them, the commonly used polymer materials are PTFE, PVDF, FEP, Kapton, nylon, PDMS, Ecoflex, silicone rubber, and etc. [75][76][77][78][79][80][81][82] At initial stage of the development of TENG, polymer materials are usually used as thin films for simple operation, however, with more advanced technology have been introduced, fiber-like polymer materials have been fabricated for the manufacture of some textile-based TENG and wearable sensors. [79,[83][84][85][86]…”
Section: Traditional Polymer Materialsmentioning
confidence: 99%
“…Among them, the commonly used polymer materials are PTFE, PVDF, FEP, Kapton, nylon, PDMS, Ecoflex, silicone rubber, and etc. [75][76][77][78][79][80][81][82] At initial stage of the development of TENG, polymer materials are usually used as thin films for simple operation, however, with more advanced technology have been introduced, fiber-like polymer materials have been fabricated for the manufacture of some textile-based TENG and wearable sensors. [79,[83][84][85][86]…”
Section: Traditional Polymer Materialsmentioning
confidence: 99%
“…A mixed-abrasive slurry (MAS) contains two or more types of solid-phase abrasives, [91] including ZrO 2 /SiO 2 , nano-diamond/ SiO 2 , polymeric magnesium iron aluminum zinc silicate/ SiO 2 , SiO 2 /CeO 2 , and ZrP/Al 2 O 3 . [92][93][94][95][96] Compared with the single-abrasive slurry, a MAS exhibits better CMP performance. It has been found that adding 10 wt% diamond abrasives to SiO 2 slurry could increase the MRR from 60 to 600 nm h −1 and reduce the Ra from 68.3 to 0.55 nm.…”
Section: Mixed-abrasive Slurrymentioning
confidence: 99%
“…The TENG output performance depends on triboelectrification contact and electrostatic induction between triboelectric materials [ 20 , 21 ]. Thus, this performance can be modified due to the surface charge density, contact area, thickness, and gap of the triboelectric layers and the operating frequency and force applied to the triboelectric materials [ [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%